Comparison of Qualitative and Volumetric Assessments of Breast Density and Analyses of Breast Compression Parameters and Breast Volume of Women in Bahcesehir Mammography Screening Project - Gemici, Aysegul Akdogan; Aribal, Erkin; Ozaydin, Ayse Nilufer; Gurdal, Sibel Ozkan; Ozcinar, Beyza; Cabioglu, Neslihan; Ozmen, Vahit (GALENOS YAYINCILIK, 2020)
Objective: We aimed to compare visual and quantitative measurements of breast density and to reveal the density profile with compression characteristics. Materials and Methods: Screening mammograms of 1399 women between May 2014 and May 2015 were evaluated by using Volpara 4th and 5th version. First 379 mammograms were assessed according to ACR BI-RODS 4th- edition and compared to Volpara. We categorized the breast density in two subgroups as dens or non-dens. Two radiologists reviewed the images in consensus. Agreement level between visual and volumetric methods and volumetric methods between themselves assessed using weighted kappa statistics. Volpara data such as fibroglandular volume (FGV), breast volume (BV), compression thickness (CT), compression force (CF), compression pressure (CP) were also analyzed with relation to the age. Results: 1399 mammograms were distributed as follows: 12.7\% VDG1, 39.3\% VDG2, 34.1\% VDG3, 13.9\% VDG4 according to the 4th edition of Volpara

1.2\% VDC1, 46\% VDG2, 36.8\% VDG3, 15.9\% VDG4 according to the 5 -5 edition of Volpara. The difference between two editions was 4.7\% increase in dense cat. -gory. 379 mammograms, according to ACR BI-BADS 4th edition, were distributed as follows: 25.9\% category A, 50.9\% category B, 19.8\% category C, 3.4\% category D. The strength of agreement between the Volpara 4th and 5th editions was found substantial (k= 0.726). The agreements between visual assessment and both Volpara editions were poor (k=- 0.413, k-0.399 respectively). There was a 142\% increase in dense group with the VDG 4th edition and 162\% with the VDG 5th edition when compared to visual assessment. Compression force decreased while compression pressure increased with incasing Volpara Density Grade (VDG) (p for trend <0.001 for both). Compression thickness and breast volume decreased with increasing VDG (p for trend <0.001 for both).The FGV decreases with age and the breast volume increases with increasing age (p<0.001). Conclusion: Visual assessment of breast density doesn't correlate well with volumetric assessments. Obtaining additional information about physical parameters and breast profile by the results of quantified methods is important for breast cancer risk assessments and prevention strategies.
Keywords: BI-RADS; Breast density; mammography; screening; Volpara